2022
DOI: 10.3390/jpm12081209
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression and Methylation Analysis of Melanoma in TCGA Database to Further Study the Expression Pattern of KYNU in Melanoma

Abstract: Background: The aim of this study was to analyze and compare melanoma gene expression profiles in TCGA database through the application of different genes to explore the pathogenesis of melanoma. Furthermore, we confirmed the extent of the role of KYNU in melanoma and whether it can be a potential target for the diagnosis and treatment of melanoma. Methods: The gene expression profiles of melanoma samples were downloaded from TCGA database, and matrix files were synthesized to screen differential genes. The Ky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A similar molecular mechanism of KYN activity was previously revealed in melanoma A375 and RPMI-7951 cells (Walczak et al 2020a ). Moreover, bioinformatics analysis confirmed the interactions between the kynurenine pathway, cyclin D1, and CDK4 in melanoma (Wang et al 2022 ). Interestingly, the gene expression data suggested that the biological activity of KYN was the result of its influence on gene expression and protein products.…”
Section: Discussionmentioning
confidence: 89%
“…A similar molecular mechanism of KYN activity was previously revealed in melanoma A375 and RPMI-7951 cells (Walczak et al 2020a ). Moreover, bioinformatics analysis confirmed the interactions between the kynurenine pathway, cyclin D1, and CDK4 in melanoma (Wang et al 2022 ). Interestingly, the gene expression data suggested that the biological activity of KYN was the result of its influence on gene expression and protein products.…”
Section: Discussionmentioning
confidence: 89%
“…This practicality and fast turnaround enable prompt clinical testing. The versatility of IHC for evaluating para n-embedded and frozen tissue slices allows important historical materials to be studied in addition to new samples 38,39 . This study is limited by the small number of patients who were analysed.…”
Section: Discussionmentioning
confidence: 99%
“…This practicality and fast turnaround enable prompt clinical testing. The versatility of IHC for evaluating paraffin-embedded and frozen tissue slices allows important historical materials to be studied in addition to new samples 38 , 39 . This study is limited by the small number of patients who were analysed.…”
Section: Discussionmentioning
confidence: 99%